Binary Cellulose Nanocrystal Blends for Bioinspired Damage Tolerant Photonic Films. (4th May 2018) - Natarajan, Bharath; Krishnamurthy, Ajay; Qin, Xin; Emiroglu, Caglar D.; Forster, Amanda; Foster, E. Johan; Weder, Christoph; Fox, Douglas M.; Keten, Sinan; Obrzut, Jan; Gilman, Jeffrey W.
Abstract: Most attempts to emulate the mechanical properties of strong and tough natural composites using helicoidal films of wood‐derived cellulose nanocrystals (w‐CNCs) fall short in mechanical performance due to the limited shear transfer ability between the w‐CNCs. This shortcoming is ascribed to the small w‐CNC‐w‐CNC overlap lengths that lower the shear transfer efficiency. Herein, we present a simple strategy to fabricate superior helicoidal CNC films with mechanical properties that rival those of the best natural materials and are some of the best reported for photonic CNC materials thus far. Assembling the short w‐CNCs with a minority fraction of high aspect ratio CNCs derived from tunicates (t‐CNCs), we report remarkable simultaneous enhancement of all in‐plane mechanical properties and out‐of‐plane flexibility. The important role of t‐CNCs is revealed by coarse grained molecular dynamics simulations where the property enhancement are due to increased interaction lengths and the activation of additional toughening mechanisms. At t‐CNC contents greater than 5% by mass the mixed films also display UV reflecting behaviour. These damage tolerant optically active materials hold great promise for application as protective coatings. More broadly, we expect the strategy of using length‐bidispersity to be adaptable to mechanically enhancing other matrix‐free nanoparticle ensembles. Abstract : A simple green strategy to fabricate helicoidal cellulose nanocrystals (CNC) films with superior mechanical properties is presented . Remarkable synergistic enhancements in modulus, strength, ductility, and toughness are obtained by incorporating long tunicate derived CNCs into chiral nematic wood films. These damage tolerant optically active materials show promise for application as protective coatings in the automobile, aerospace, electronics, and infrastructure industries.